EFEKTIVITAS MANAJEMEN PEMBIAYAAN SYARIAH DALAM MENGEMBANGKAN SEKTOR RIIL - Wa Ode Jeslin; Ahmad Ramdhani Mungkur; Mella Afrina; Muhammad Ikhsan Harahap (INTERNATIONAL, Journal of Sharia Business Management, 2025)
This study aims to analyze the effectiveness of Islamic financing management in developing the real sector in Indonesia. The research employs a qualitative descriptive approach through an extensive literature review of academic journals, financial institution reports, and official policy documents related to Islamic finance. The findings indicate that Islamic financing significantly strengthens the real sector foundation through partnership-based contracts such as mudharabah and musyarakah, which enhance MSME productivity and create new employment opportunities. Moreover, fiscal instruments such as Sukuk Negara (Islamic Sovereign Bonds) play a pivotal role in financing national development projects that are productive, sustainable, and compliant with Islamic principles. The main challenges include limited financial literacy, lack of product innovation, and concentration of financing in specific sectors. This study concludes that the effectiveness of Islamic financing management depends not only on financial performance but also on the integration of regulatory frameworks, digital innovation, and public literacy. Therefore, synergy between fiscal, monetary, and Islamic financial institutions is essential to realize a fair, productive, and sustainable Islamic economy in Indonesia.